SPATIAL PATTERN OF BOKO HARAM ATTACKS AND FATALITIES AND TOURISM BUSINESSES ACROSS STATES IN THE NORTH EASTERN NIGERIA - Inyang, Oduduabasi; Olanrewaju Lawal, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study was on the spatial exploration of Boko Haram terrorist attacks and its influence on components of tourism businesses (hotels) in Northeastern Nigeria. Secondary data on location, nature, date, and number of fatalities from the Boko Haram attack were sourced from Armed Conflict Location & Event Data (ACLED). Data on the location of hotels were sourced from the field with the use of the Geographic Positioning System (GPS). A total of 558 hotels were selected in a one-stage cluster sampling technique. The study adopts a longitudinal research design where centrographic analysis was carried out to describe the spatial distribution of events. Results of the study revealed that Boko Haram attacks were more coordinated rather than a random occurrence with most of the attacks concentrated in Borno State. Furthermore, Boko Haram did not directly target tourism businesses though some of the hotels fell within a 1.5km radius of the attacks. The study, therefore, recommends for an intense media promotion of the areas and States not majorly affected by the crisis, rebuilding of areas and States recovered from the group, provisions of more resilient security apparatus, and general development of social, educational, and economic infrastructures to help revamp not only the tourism sector of the area but its general socioeconomic activities.